Pathological response and efficacy of neoadjuvant carboplatine in early triple negative breast cancer - عبدالله نادر (Latakia University Journal -Medical Sciences Series, 2021)
Several recent international studies showed that adding carboplatin to anthracyclines and taxanes improves the rate of complete pathological response in triple negative breast cancer This retrospective study aims to evaluate the role of carboplatin by adding it to taxanes (docetaxel, paclitaxel) in early triple-negative breast cancer patients treated with chemotherapy before surgery in terms of pathological response rate. The study included 54 patients who attended the Chemotherapy and Radiotherapy Center in Tishreen Hospital between March 2016 and January 2020 with non-metastatic triple negative breast cancer (hormone receptor negative (ER-,PR-) and anti-membrane receptor 2 negative (HER2-)) with Tumor size ≥ 2 cm and/or clinically palpable lymph node enlargement. All patients were treated before surgery (4 doses of AC with 4 doses of carboplatin added to it (docetaxel/paclitaxel weekly or every three weeks). A complete pathological response rate was observed in 25 patients ( 46.3%), partial pathological response in 24 patients ( 44.4%), while a progression in 5 patients with a rate of 9.3%. The response was better in postmenopausal women who had ductal carcinoma, with tumor size between (2-5 cm) and negative lymph nodes with a statistically significant difference. The best combination was between carboplatin and weekly paclitaxel, where the complete pathological response occurred in 18 patients (72%), while the complete response occurred in 6 patients (24%) when carboplatin and docetaxel combined. The worst combination of carboplatin and paclitaxel every three weeks, with a complete pathological response in one patient (4%) , without a statistically significant difference between the three protocols. The addition of carboplatin to taxanes, especially weekly paclitaxel, is an important treatment option in patients with early triple negative breast cancer who are candidates for neo adjuvant chemotherapy.